SOCIAL AND POLITICAL DEVELOPMENT OF KABARDINO-BALKARIA DURING THE PERIOD OF SYSTEM TRANSFORMATIONS OF THE RUSSIAN SOCIETY - Tetuev, A I (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the evolution of the forms of statehood of Kabardino-Balkaria people in the conditions of system transformations of the Russian society. The author considers ethnopolitical processes and centrifugal tendencies at the stage of “sovereignization” of the Russian autonomies. The author analyzes the role of the Federal Treaty in preserving unity of Russia,the peculiarities ofreforming of the regional public authorities and the problems of bringing the republic’s legislation in line with the Constitution of the Russian Federation. The author also generalizes the experience of public authorities in supporting social and political stability in the region.
Keywords: people; sovereignty; republic; centrifugal tendencies; statehood; reforming; constitution; parliament; local government; stability